Determinant Factors of Work Stress Risk in Nurses at Rahman Rahim Sidoarjo Hospital - Irma Nur Khoiriah (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: Health sector such as hospitals had to pay attention to the company's hygiene aspects and all over occupational health. Nurses were one of the health worker that interact directly with patients and their families. Nurses were very risky to experience work stresses because they had complex tasks and very high responsibilities for the safety of human lives. The purpose of this study was determining factors of work stress in nurses at Rahman Rahim Sidoarjo Hospital. Methods: This research was a cross sectional research design. This study used the entire population of nurses at Rahman Rahim Sidoarjo Hospital, which consists of 60 people. The object of research was Rahman Rahim Sidoarjo Hospital. Research variables included the level of risk of work stress, sex, age, personality, working period social support and subjective workload. Results: The research study shows that most of the nurses at Rahman Rahim Sidoarjo Hospital have moderate stress risk levels of 44 out of 60 nurses (73.3%). A small number of nurses had a low level of stress risk of 11 nurses (18.3%), a high level of stress risk as many as 5 nurses (8.4%), and no nurses who had a high level of risk of work stress were found. Conclusion: Determinant factors of work stress risk that play an important role are factors of sex, personality and working period.Keywords: determinant factor, nurses, work stress